Estudo do papel do receptor ativado por protease (PAR)-2 no recrutamento de eosinófilos induzido por triptase em modelo de pleurisia em camundongos - Natalia Alves de Matos (2013)
Proteinase-activated receptors (PAR) are part of a family of G-protein-coupled receptors that are activated by serine proteases via proteolytic cleavage of a specific sequence of amino acids in N-terminal portion, and its activation has been associated with the regulation of different inflammatory phenomena. These receptors were classified from 1 to 4 by order of discovery, have structural similarities but also have differences in the group N-terminal and the serine-protease responsible for cleavage. PAR-2 is expressed in the airways, the epithelium, endothelium and smooth muscle tissue of the lung, trachea and bronchial fibroblasts and inflammatory cells such as mast cells and eosinophils. In recent years, studies have shown the involvement of PAR-2 in the recruitment and activation of leukocytes, however, although there are few studies in the literature showing the presence and activation of PAR-2 in eosinophils, the mechanisms involved in molecular signaling triggered by activation of this receptor by their respective agonists are not well understood. Our objective was to evaluate the role of PAR-2 in the control of eosinophil recruitment in experimental pleurisy, as well as the participation of mast cell tryptase and its importance in inhibiting this phenomenon. The experimental protocols were approved by the animal ethics committee (CEUA / UFMG, 193/2012). After the treatment protocol, mice were sacrificed in a CO2 chamber, and pleural lavage was collected for further analysis in the proper times. One-Way ANOVA followed by Newman-Keuls post-test was used for analysis of cell migration and Student's t test for analysis of western blotting. Intrapleural (i.pl.) injection in naive BALB/c mice with selective agonist of PAR-2 SLIGRL-NH2 (30 g), or mast cell tryptase (300 ng) or ovalbumin (OVA; 1 g) in animals previously sensitized to this antigen, induced eosinophil recruitment into the pleural cavity of these animals. Thus, mice were injected i.pl. with selective antagonist of PAR-2 ENMD1068 (3 g) 15 minutes before the i.pl. injection OVA (1g) in mice immunized; or with mast cell tryptase (300 ng) and eotaxin-1 (100 ng) in naive mice to study the role of the PAR-2 in the recruitment of eosinophils. The ENMD1068 inhibited eosinophilia induced by OVA (97%), by tryptase (87%), and also by eotaxin-1 (61%), suggesting the involvement of PAR-2 activation in the recruitment of eosinophils induced by these stimuli. Otherwise, in mice treated with tryptase (300 ng) we evaluated receptor expression 4, 8, 24 and 48 hours after stimulation i.pl., using western blotting. The results demonstrated increased receptor expression 24 and 48 hours after treatment compared to their respective controls in leukocytes obtained pleural lavage. Furthermore, immuno-histochemical tests have demonstrated co-localization of the receptor PAR-2 in the membrane and cytoplasm of eosinophils and mononuclear cells 24 and 48 hours after i.pl. challenge with tryptase. Once demonstrated the involvement of PAR-2 in eosinophil recruitment induced by tryptase we evaluated the importance of endogenous tryptase to the recruitment of eosinophils in the pleurisy model, and the pre-treatment with APC366 (5 mg/kg), a selective inhibitor of tryptase, decreased the recruitment of eosinophils induced by SLIGRL-NH2 (30 g) and eotaxin-1 (100 ng). In conclusion, our results suggest a role of PAR-2 activation in the control of eosinophils recruitment and thus in the development of the inflammatory response in the pleural cavity. The present study contributes to the understanding of the mechanisms involved in eosinophilia, suggesting the blockage of PAR-2 as a new therapeutic strategy for its control. Financial support: CNPq/CAPES/ FAPEMIG.